10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
Background Board of Pharmacy Specialties (BPS) board certification represents a recognized standard for advanced pharmacy practice and provides formal validation of specialized knowledge and skills through rigorously developed examinations. In other health professions, taking certification or licensure examinations soon after completing training has been associated with higher pass rates, while delays have been linked to poorer outcomes. This study investigates whether a similar pattern exists among BPS candidates, particularly those who complete residency training and become eligible for certification. Methods This study evaluates the association between time from eligibility to examination and first-attempt outcomes among residency-trained pharmacists. This cross-sectional analysis used deidentified data from the BPS MyBPS database for United States-based candidates who attained eligibility through post-graduate year one (PGY1) or post-graduate year two (PGY2) residency training and completed a first-attempt certification examination in 2025. Time to examination was defined as the number of days between residency completion and exam date and was categorized as ≤ 365 days, 366-730 days, and > 730 days. The primary outcome was examination result (pass or fail). Results Among 2598 candidates, pass rates declined as time-to-exam increased. Candidates who delayed testing beyond 2 years had significantly lower pass rates compared with those testing within 1 year (p < 0.001) and between one and 2 years (p = 0.011), while no significant difference was observed between the other two groups (p = 0.225). Conclusion Overall, longer time from eligibility to examination was associated with lower first-attempt success. These findings suggest that sitting for a BPS board certification examination within 2 years may improve outcomes and inform decision-making for candidates.